The effectiveness of Islamic comic media in increasing the attitude of healthy breakfast among students - Damayanti, Amilia Yuni; Darni, Joyeti; Hafidzatunnisa, Hafidzatunnisa (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
ABSTRAK Background: As much as 73.4% of children aged ≥ 5 years in Indonesia have breakfast with the low nutritional quality of food consumption, as evidenced by the prevalence of 95.5% of children's less consumption of vegetables and fruits. Breakfast habits affect fiber and micronutrient levels. Communication and nutritional information can increase accuracy in breakfast behavior from childhood. Effective and efficient media are needed. So far, the media for children has prioritized illustrations without paying attention to the cultivation of moral values.Objectives: This study aimed to determine the effect of Islamic comic media on improving healthy breakfast attitudes among students.Materials and Methods: The research design was a quasi-experimental type. Subjects were taken by a simple random sampling method. Ninety-six students were divided into three groups. Group A was given nutrition education using Islamic comic media about health breakfast (n = 32). Group B was given nutrition education using Islamic comic strip media about health (n = 32). Group C was a control group (n = 32). The study used two types of nutrition promotion media: comics and comic strips, which are stories about healthy eating in Islam. The time for nutrition education intervention through comics and comic strips is 2x ± 35 minutes. The pretest was ± 25 minutes with ± 10 minutes explaining the instructions for filling out the questionnaire. The posttest was ± 25 minutes with a discussion for ± 10 minutes—nutritional attitudes related to health breakfast by answering a validated questionnaire. We used the Lickert scale to categorized nutritional attitudes. Statistical test was done by Wilcoxon and Mann Whitney test.Results: The distribution of nutrition attitudes of respondents increased after the provision of Islamic comics, both comics and comic strips about breakfast. The nutritional attitudes increased significantly in the Islamic comic media group (p = 0.000) and the Islamic comic strip media group (p = 0.000), from 78.75 to 92.96 and 78.61 to 92.88, respectively.Conclusions: There was a relationship between counseling and Islamic comic media regarding healthy breakfast towards the nutritional attitude of elementary school-age students.